Humanized Mice Reveal New Insights Into the Thymic Selection of Human Autoreactive CD8+ T Cells - Li, Yang; Teteloshvili, Nato; Tan, Shulian; Rao, Samhita; Han, Arnold; Yang, Yong-Guang; Creusot, Rémi J. (Frontiers in Immunology, 2019)
Thymic selection constitutes the first checkpoint in T-cell development to purge autoreactive T cells. Most of our understanding of this process comes from animal models because of the challenges of studying thymopoiesis and how T cell receptor (TCR) specificity impacts thymocyte phenotype in humans. We developed a humanized mouse model involving the introduction of autoreactive TCRs and cognate autoantigens that enables the analysis of selection of human T cells in human thymic tissue in vivo. Here, we describe the thymic development of MART1-specific autoreactive CD8+ T cells that normally escape deletion and how their phenotype and survival are affected by introduction of the missing epitope in the hematopoietic lineage. Expression of the epitope in a fraction of hematopoietic cells, including all major types of antigen-presenting cells (APCs), led to profound yet incomplete deletion of these T cells. Upregulation of PD-1 upon antigen encounter occurred through the different stages of thymocyte development. PD-1 and CCR7 expression were mutually exclusive in both transgenic and non-transgenic thymocytes, challenging the view that CCR7 is necessary for negative selection in humans. In the presence of antigen, MART1-reactive T cells down-regulated TCR, CD3, CD8 and CD4 in the thymus and periphery. Moreover, expression of secondary TCRs influences MHC class I-restricted T cells to develop as CD4+, particularly regulatory T cells. This new model constitutes a valuable tool to better understand the development of autoreactive T cells identified in different human autoimmune diseases and the role of different APC subsets in their selection.